ECONOMIC SANCTIONS AS A CONCEPT OF POWER POLITICS - I. N. Timofeev (Vestnik MGIMO-Universiteta)
The purpose of the article is to conceptualize economic sanctions in terms of international power politics. Legal and economic literature study sanctions by means of legal norms analysis and their impact on economies, companies and corporations. However, this approach misses a political component, specially the one of coercion to comply with international norms or requirements of sanctions’ initiators. Usually sanctions are an instrument of economically advanced states vis a vis developing countries with fragile or vulnerable economy. The very essence of sanctions is determined by the asymmetry of international system in terms of economic capabilities. Such an asymmetry fuels a debate between those who consider sanctions as an effective and legitimate instrument (US, EU and other developed states) and those who believe that only the UN Security Council can be a legal source of sanctions, while others are illegal (supported by Russia, China and several dozens of developing countries). This debate reflects a cleavage on a more fundamental problem – the one of sovereignty and the right to interfere into sovereign affairs of states. Recognition of sanctions’ legitimacy would mean the recognition of the right to interfere into sovereign affairs of the target-states beyond the UN Charter. The article provides a reflection of this debate, stressing on different interpretations of the concept of sanctions.The article makes a distinction between the concept of sanctions and the concept of trade wars. Such disengagement is critically important for understanding sanctions as a political concept. If trade wars are conducted to maximize profits, economic sanctions are used to achieve political goals. This determines the fundamental difference in the relations between business and government: in the case of trade wars, business is the main lobbyist for decisions of state bodies, in case of sanctions, the government is the initiator, and business is forced to adapt to the current situation. In the first case, business acts as a subject, in the second - as an object.